A novel and efficient method for calculating beam shadows on exterior surfaces of buildings in dense urban contexts. (1st February 2023) - Wang, Xiaoyu; Zhang, Xinkai; Zhu, Sijie; Ren, Jiawen; Causone, Francesco; Ye, Yu; Jin, Xing; Zhou, Xin; Shi, Xing
Abstract: To address the challenges associated with the efficiency of calculating beam shadows on building exterior surfaces in dense urban contexts being low, a novel "neighbourhood shading building surfaces" determination criterion is proposed. The criterion was applied to the beam shadow calculation methods to evaluate its effectiveness in two case studies, one fictitious and simplified and the other real and complex. The results show that the novel criterion can efficiently and precisely determine the neighbourhood building surfaces that may shade the target buildings compared with the existing one. In addition, the efficiency of calculating beam shadows on building exterior surfaces in dense urban contexts is significantly enhanced after applying the novel determination criterion. Compared with the shadow calculation methods without neighbourhood judgement, the calculation accuracy is similar, while the total shadow calculation time is reduced by approximately 92% when the proposed criterion is integrated. Compared with the shadow calculation methods using the existing neighbourhood judgement criterion, both the calculation accuracy and efficiency are improved when the proposed criterion is integrated, showing a 68% reduction in the total shadow calculation time. It is also demonstrated that the analytical method (i.e., the polygon clipping method) integrated with the new criterion is more efficient and accurate for calculating beam shadows on exterior surfaces of buildings in dense urban contexts. Highlights: A novel "neighbourhood shading building surfaces" determination criterion is proposed. Effectiveness of new criterion applied to common shadow calculation methods was evaluated. The novel determination criterion is more accurate and efficient than the existing one. Efficiency of shadow calculation is significantly enhanced by using the novel criterion. Polygon clipping method integrated with the novel criterion is more efficient and accurate.